2022
DOI: 10.2147/idr.s374805
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Trends of the Most Common Causative Pathogens Associated with Community-acquired Respiratory Infections in China: 2009–2018

Abstract: Background Emergence of antimicrobial resistance poses new challenges in the management of community acquired respiratory tract infections (CARTIs). Therefore, surveillance on the antimicrobial susceptibilities of common respiratory pathogens is valuable and guides empirical therapeutic choices in management of CARTIs. Objective The objective of the current study is to summarize the antimicrobial resistance trends in common respiratory tract pathogens isolated from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…M. catarrhalis showed 73.3%, 60.0%, and 53.3% resistance rates to azithromycin, erythromycin, and trimethoprim-sulfamethoxazole, whereas P. aeruginosa showed 45.5% resistance rate to cefepime. In contrary with our findings, a study done in China showed a high level of sensitivity of M. catarrhalis to azithromycin, 100%, and trimethoprim-sulfamethoxazole, 67.7% [ 11 ]. The higher resistance pattern observed in this study could be associated with several factors, including the widespread irrational use of drugs prior to patients visiting health facilities and the increasing circulation of drug-resistant isolates in the community warranting continues monitoring of the resistance profile in the community.…”
Section: Discussioncontrasting
confidence: 99%
“…M. catarrhalis showed 73.3%, 60.0%, and 53.3% resistance rates to azithromycin, erythromycin, and trimethoprim-sulfamethoxazole, whereas P. aeruginosa showed 45.5% resistance rate to cefepime. In contrary with our findings, a study done in China showed a high level of sensitivity of M. catarrhalis to azithromycin, 100%, and trimethoprim-sulfamethoxazole, 67.7% [ 11 ]. The higher resistance pattern observed in this study could be associated with several factors, including the widespread irrational use of drugs prior to patients visiting health facilities and the increasing circulation of drug-resistant isolates in the community warranting continues monitoring of the resistance profile in the community.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with prior studies 14 , 26 , 30 , 31 , our study noted minimal resistance to rifamycins, fluoroquinolones, and third-generation cephalosporins. H. influenzae isolates resistant to fluoroquinolones are generally uncommon in children and have been mainly isolated from older people with chronic lung diseases exposed to frequent quinolone treatments 32 34 .…”
Section: Discussionsupporting
confidence: 92%
“… 8 , 25 However, in contrast to pediatric patients, the resistance of Streptococcus pneumoniae to common antibiotics was increasing over time in adult patients from 2009 to 2018, in a tertiary hospital in Beijing, China, with patients aged <18 years old excluded from study. 26 …”
Section: Discussionmentioning
confidence: 99%